ANCAMAN DAN KEPUNAHAN BURUNG MAMBRUK POLOS Goura cristata DI BAGIAN TIMUR KEPALA BURUNG (VOGELKOP) IRIAN JAYA BARAT - Agustinus Kilmaskossu (Jurnal Natural, 2007)
The three species of “mambruk” (crowned pidgeons) are endemic to New Guinea (Irian Jaya and the Papua Nugini). The species are listed in CITES as vulnerable. In Indonesia the species are protected by law, but in the field they are still being hunted. There fore, the threat and extinction of the species was observed on five location in the Birds Head Region of Papua. The observation indicated thet there was only are location was the estuary of Warmiseru and Suandei Lagoon where the spesies were relativety observed.